Health-related quality of life and nutrient intake of the elderly with type 2 diabetes according to comorbidity burden: a cross-sectional study - Yejung Choi; Kyong Park (Korean Journal of Community Nutrition)
Objectives This study aimed to explore the cross-sectional association between health-related quality of life (HRQoL) according to the number of comorbidities in older adults with type 2 diabetes mellitus (T2DM) using the Euro Quality of Life-5 Dimensions (EQ-5D) index. Methods This study included 3,553 participants aged ≥ 65 years from the 2008–2020 Korea National Health and Nutrition Examination Survey. Dietary data were collected through 24-hour recall interviews by trained researchers, and demographic and lifestyle information via self-administered questionnaires. HRQoL was measured using a modified EQ-5D scale. Multivariable linear regression analyzed the associations between EQ-5D scores, nutrients and comorbidity, controlling for sociodemographic and health variables. Results Most participants reported ‘no problems’ in the EQ-5D scores, although approximately 17% to 47% of participants reported ‘some problems’ or ‘extreme problems,’ depending on the dimension. As comorbidities increased, significant declines were observed across all dimensions, particularly in mobility, usual activities, pain/discomfort, and anxiety/depression. Nutrient intake analysis revealed that participants with three or more comorbidities consumed less carbohydrates, but more fat. Conclusion Our findings demonstrate that among older adults with T2DM, a higher number of comorbidities is associated with decreased HRQoL. Additionally, there are differences in nutrient intake patterns among those with more comorbidities, specifically decreased carbohydrate intake and increased fat intake. These results emphasize the need for comprehensive and tailored management strategies that consider both diabetes and the co-occurring health conditions. By addressing the complex healthcare needs of individuals with multiple comorbidities, it is possible to enhance their HRQoL and overall well-being.